2010
DOI: 10.1007/s11102-010-0265-0
|View full text |Cite
|
Sign up to set email alerts
|

Carotid atheromatic plaque is commonly associated with hypopituitary men

Abstract: Hypopituitarism increases the risks of many cardiovascular conditions and therefore, patients with this disease are more prone to cardiovascular disease. To our knowledge, there have been few studies on carotid artery plaque in male patients with hypopituitarism in assessing cardiovascular risks. The aim of this study was to specifically compare carotid artery plaque while examining other major cardiovascular risk factors between male patients with hypopituitarism and control subjects. Forty male patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…These numbers are higher than in the general population and similar to that of Deepak et al[23] who evaluated 152 adults with hypothalamic-pituitary disease, 89 with nonfunctioning adenomas and adenomas associated with acromegaly and Cushing's disease, and reported obesity in 50% of the sample and overweight in 30.8%. Kim et al[24] evaluated 40 men with hypopituitarism, and 70% of them had pituitary adenoma. They reported an average BMI of 25.3, close to our finding of 27.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers are higher than in the general population and similar to that of Deepak et al[23] who evaluated 152 adults with hypothalamic-pituitary disease, 89 with nonfunctioning adenomas and adenomas associated with acromegaly and Cushing's disease, and reported obesity in 50% of the sample and overweight in 30.8%. Kim et al[24] evaluated 40 men with hypopituitarism, and 70% of them had pituitary adenoma. They reported an average BMI of 25.3, close to our finding of 27.5.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hypopituitarism did not interfere with the results of WC and WHR in the current series, although the small number of hypopituitary patients (13) may be a limiting factor of this analysis. Kim et al[24] observed higher WC (87.5 ± 0.77) e WHR (0.91 ± 0.01) values in patients with hypopituitarism than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery atheromatous plaques were observed more frequently in hypopituitary subjects than age-and sex-matched controls (59⅐5% vs. 2⅐5%, P Ͻ 0⅐01) (23). Significantly higher proportion of patients with hypopituitarism also had metabolic syndrome compared to the normal population, making them more prone to develop premature atherosclerosis (23,24). Increased risk of atherosclerosis and strokes had been demonstrated in patients who had cranial irradiation for other reasons (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition over-replacement with GC (29, 30) and sex steroid deficiency contribute to impaired metabolic parameters and atherogenesis in such patients (15). In a large study, atherosclerotic plaques in carotid arteries were present in half of the patients with hypopituitarism (31). Coronary flow reserve (CFR), as measured by transthoracic color echocardiography is a simple measurement of blood flow in coronary arteries, is impaired in subjects with GH deficiency, and corelates with serum IGF-1 concentration (32).…”
Section: Risk Factors Of CV Diseases In Hypopituitarism and Ssmentioning
confidence: 99%